IVUS-assisted parallel wiring for coronary chronic total occlusion - Taniguchi, Yousuke; Sakakura, Kenichi; Ban, Soichiro; Fujita, Hideo (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2022)
In percutaneous coronary intervention (PCI) for chronic total occlusion (CTO), various techniques such as parallel wiring or intravascular ultrasound (IVUS)-guided wiring have been developed. If the first guidewire goes into the subintimal space (Figure 1 A), parallel wiring is an option. The main drawback in parallel wiring is the lack of information where the first guidewire went into the subintimal space, i.e., near the distal cap (Figure 1 B), near the proximal cap (Figure 1 C), or somewhere in the middle (Figure 1 D). Although IVUS-guided wiring can provide information where the first guidewire went into the subintimal space, IVUS-guided wiring has been considered as a last resort in several algorithms for crossing the CTO [1], partly because IVUS-guided wiring requires expansion of the subintimal space by small balloon dilatation. Recently, a small profile IVUS catheter has been developed. In this case report, we describe IVUS-assisted parallel wiring technique, in which a small profile IVUS catheter was used just before parallel wiring.